Ministerial decrees Nos.371-374/2013 on the commitment to produce and import according to the Egyptian standard specifications / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Ministry of Industry and foreign Trade Decree No. 371 for the Year 2013 – Ministry of Industry and foreign Trade Decree No. 374 for the Year 2013 قرارات وزارة الصناعة والتجارة الخارجية قرار رقم 371 لسنة 2013 – وزارة الصناعة والتجارة الخارجية قرار رقم 374 لسنة 2013